From the Treaty of Versailles to the Treaty of Maastricht - Holmes, Martin, 1954 April 26- author.
1 online resource
Keywords: "This book examines European history and politics between two very well-known but flawed treaties: The Treaty of Versailles and the Treaty of Maastricht. From the Treaty of Versailles to the Treaty of Maastricht will appeal to researchers and students alike interested in European history, politics and World War I and II"--